Thymidylate synthase gene variants as predictors of clinical response and toxicity to fluoropyrimidine-based chemotherapy for colorectal cancer - Castro Rojas, Carlos Andrés; Esparza Mota, Antonio R.; Hernández Cabrera, Francisco; Romero Díaz, Víktor J.; González Guerrero, Juan Francisco; Maldonado Garza, Héctor Jesús; García González, Irma S.; Buenaventura Cisneros, Sergio; Sanchez Lopez, Josefina Y.; Ortiz López, Rocío; Camacho Morales, Alberto; Barboza Quintana, Oralia; et al. (2017)
Abstract Background: Fluoropyrimidines form the chemotherapy backbone of advanced and metastatic colorectal cancer (CRC). These drugs are frequently associated with toxicity events that result in dose adjustments and even suspension of the treatment. The thymidylate synthase (TYMS) gene is a potential marker of response and toxicity to fluoropyirimidines as this enzyme is the molecular target of these drugs. Our aim was to assess the association between variants of TYMS with response and toxicity to fluoropyrimidines in patients with CRC in independent retrospective and prospective studies. Methods: Variants namely rs45445694, rs183205964, rs2853542 and rs151264360 of TYMS were genotyped in 105 CRC patients and were evaluated to define their association with clinical response and toxicity to fluoropyrimidines. Additionally, the relationship between genotypes and tumor gene expression was analyzed by quantitative polymerase chain reaction. Results: The 2R/2R (rs45445694) was associated with clinical response (p = 0.05, odds ratio (OR) = 3.45) and severe toxicity (p = 0.0014, OR = 5.21, from pooled data). Expression analysis in tumor tissues suggested a correlation between the 2R/2R genotype and low TYMS expression. Conclusions: The allele 2R (rs45445694) predicts severe toxicity and objective response in advanced CRC patients. In addition, the alleles G(rs2853542) and 6bp-(rs151264360) are independent predictors of response failure to chemotherapy. This is the first study made on a Latin American population that points out TYMS gene variants have predictive values for response and toxicity in patients with CRC treated with fluoropyrimidine-based chemotherapy.